PELAKSANAAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DAN KAITANNYA DENGAN PENDIDIKAN AKHLAK ANAK DALAM HADITS - Wirda Ningsih; Yundri Akhyar (Universitas Tribhuwana Tunggadewi, 2024)
The purpose of this study is to investigate the implementation of the project at SDIT Future Islamic School (FIS) Pekanbaru to enhance the Pancasila student profile (P5) dimension of faith, devotion to God Almighty, and noble character in the independent curriculum, as well as the relationship between this project and the students' moral education in the hadith. The study that was done falls under the category of qualitative descriptive research. Interviews are the method used to get data. Content analysis is the method used for data analysis. According to the study's findings, P5 is being implemented at SDIT Future Islamic School (FIS) Pekanbaru, which is improving religious, interpersonal, environmental, and national morality. The moral education of children in the hadith is connected to the implementation of P5 at SDIT FIS. The result of the research is Islamic Integrated Islamic School should adopt the hadist in their teaching learning process.